1995
DOI: 10.1093/ije/24.3.504
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Cigarette Smoking and Each of 21 Types of Cancer: A Multi-Site Case-Control Study

Abstract: Of the 21 types of cancer examined, the following were associated with smoking among men in Montreal: lung (including all major histological subtypes), bladder (and its main histological subtypes), oesophagus, stomach and pancreas. Smoking likely accounts for a large proportion of cancers occurring at these sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
62
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(68 citation statements)
references
References 32 publications
5
62
0
1
Order By: Relevance
“…Out of the 11 reporting an increased risk (Hammond and Horn, 1958;Paffenbarger Jr et al, 1977;Williams and Horm, 1977;Matthews et al, 1984;McLaughlin et al, 1995;Siemiatycki et al, 1995;Adami et al, 1998;Stagnaro et al, 2001;Briggs et al, 2002;Glaser et al, 2004;Nieters et al, 2005), three presented significant results (McLaughlin et al, 1995;Briggs et al, 2002;Nieters et al, 2005), among which one is part of our research (Nieters et al, 2005). These studies were characterised by small sample size, 10 of the 15 studies being based on less than 200 case -control pairs.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Out of the 11 reporting an increased risk (Hammond and Horn, 1958;Paffenbarger Jr et al, 1977;Williams and Horm, 1977;Matthews et al, 1984;McLaughlin et al, 1995;Siemiatycki et al, 1995;Adami et al, 1998;Stagnaro et al, 2001;Briggs et al, 2002;Glaser et al, 2004;Nieters et al, 2005), three presented significant results (McLaughlin et al, 1995;Briggs et al, 2002;Nieters et al, 2005), among which one is part of our research (Nieters et al, 2005). These studies were characterised by small sample size, 10 of the 15 studies being based on less than 200 case -control pairs.…”
mentioning
confidence: 84%
“…Sixteen epidemiological studies have investigated the effect of tobacco smoking on HL (Hammond and Horn, 1958;Newell et al, 1973;Paffenbarger Jr et al, 1977;Williams and Horm, 1977;Abramson et al, 1978;Matthews et al, 1984;Bernard et al, 1987;McLaughlin et al, 1995;Siemiatycki et al, 1995;Adami et al, 1998;Miligi et al, 1999;Stagnaro et al, 2001;Briggs et al, 2002;Gallus et al, 2004;Glaser et al, 2004;Nieters et al, 2005). Out of the 11 reporting an increased risk (Hammond and Horn, 1958;Paffenbarger Jr et al, 1977;Williams and Horm, 1977;Matthews et al, 1984;McLaughlin et al, 1995;Siemiatycki et al, 1995;Adami et al, 1998;Stagnaro et al, 2001;Briggs et al, 2002;Glaser et al, 2004;Nieters et al, 2005), three presented significant results (McLaughlin et al, 1995;Briggs et al, 2002;Nieters et al, 2005), among which one is part of our research (Nieters et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of lung cancer patients are smokers (4). Cigarette smoke is known to increase the carcinogen DNA-adduct levels, which in turn form aggressive tumors by mutating and thus inactivating tumor suppressor genes, such as TP53, and thereby decrease the survival rates of patients with NSCLC (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…3,4,[9][10][11][12] Increased risks were observed also for other NHL subtypes, including low-grade 6 or high-grade NHL. 5,6 However, other prospective 4,13 and case-controls studies [14][15][16][17][18][19][20][21][22] found no consistent association between tobacco and NHL risk.…”
mentioning
confidence: 99%